Sexual dimorphism in hepatic PPAR alpha and CYP4a12a expression is associated with reduced development of drug-induced non-alcoholic steatohepatitis in female IL-33−/− mice - Thomas, Chloe; Njoku, Dolores B. (Frontiers in Medicine, 2024)
Males are at higher risk for developing metabolic dysfunction-associated steatohepatitis (MASH) than females; however, mechanisms mediating sexual dimorphism in MASH development are not completely understood. Nutrition-based mouse models suggest that dysregulated fatty acid biosynthesis promotes MASH. Drugs recapitulate MASH without diet variabilities. This brief report investigates associations of sexual dimorphism with male susceptibility to MASH utilizing a drug-induced MASH model and focuses on very-long-chain fatty acid biosynthesis pathways. We assessed male and female mouse livers at 5 and 15 weeks following MASH induction by immunizations and age-matched un-immunized controls utilizing Western blot. Our results suggest that PPAR alpha and CYP4a12a protect females, while CYP4v2 does not protect males from MASH development. Our results have important implications for understanding sexual dimorphism in the pathogenesis of MASH.